Mushrooms-Rich Preparations on Wound Healing: From Nutritional to Medicinal Attributes - Sharifi-Rad, Javad; Butnariu, Monica; Ezzat, Shahira M.; Adetunji, Charles Oluwaseun; Imran, Muhammad; Sobhani, Seyyed Reza; Tufail, Tabussam; Hosseinabadi, Tahereh; Ramírez-Alarcón, Karina; Martorell, Miquel; Maroyi, Alfred; Martins, Natália (Frontiers in Pharmacology, 2020)
Mushrooms have a significant role in human diet as functional food and as a nutraceutical resource. The combination of its umami flavor, protein, vitamins, minerals and carbohydrates has meant that mushrooms could be considered a cheap food source for a long time in many countries. Moreover, mushrooms contain an excellent variety of bioactive metabolites that can be successful in both prevention and treatment of various human health hazards. In addition, extracts from medicinal mushrooms and their metabolites have been verified for wound treating with contribution to different mechanisms of the healing process; however, we must not choose the incorrect fungus, as some can be toxic. This review summarizes the nutritional value of mushrooms, ethnobiology and ethnopharmacology, their bioactive compounds, wound healing potential and safety features.